Technological Frames in the Digital Age: Theory, Measurement Instrument, and Future Research Areas - Patrick Spieth; Tobias Röth; Thomas Clauss; Christoph Klos (Journal of Management Studies, 2021)
Digital technologies fuel technological change that generates substantial uncertainty and complexity. Corporate actors rely on their technological frames to cope with these challenges. Technological frames determine how actors interpret, assess, and shape a technology's development, usage, and trajectory. However, the research fails to provide insights into the microfoundations that can explain the consequences of heterogeneity in technological frames. We argue that this research gap is due to a lack of a proper measurement instruments. To address this gap, we theorize on the antecedent of technological frames on the individual level and undertook a rigorous scale-development process encompassing five steps and samples. The resulting measurement instrument assesses five distinct but interrelated dimensions of an actor's technological frame (personal attitude, application value, organizational influence, industrial influence, and supervisor influence). This instrument provides a theoretical and methodological foundation for future research on technological frames and corporate strategizing in the digital age.
Keywords: 650; digital technology; microfoundation; organizational change; scale development; technological frame; technology implementation